Mandate-based health reform and the labor market: Evidence from the Massachusetts reform - Jonathan T. Kolstad; Amanda E. Kowalski (W.E. Upjohn Institute for Employment Research, 2015)
We model the labor market impact of the key provisions of the national and Massachusetts "mandate-based" health reforms: individual mandates, employer mandates, and subsidies. We characterize the compensating differential for employer-sponsored health insurance (ESHI) and the welfare impact of reform in terms of "sufficient statistics". We compare welfare under mandate-based reform to welfare in a counterfactual world where individuals do not value ESHI. Relying on the Massachusetts reform, we find that jobs with ESHI pay 2,812 less annually, somewhat less than the cost of ESHI to employers. Accordingly, the deadweight loss of mandate-based health reform was approximately 8 percent of its potential size.
Keywords: I13; J3; 330; Affordable Care Act; Massachusetts health reform; welfare effects